ANALISIS ISI BUKU PENDIDIKAN KEWARGANEGARAAN UNTUK PERGURUAN TINGGI: SARANA PENDIDIKAN POLITIK PEMILIH PEMULA - Rika Kartika; Siti Maizul Habibah; Ascosenda Ika Rizqi; Intan Maharani Ibrahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Amidst the growing challenge of rising voter abstention (Golput) in every General Election (Pemilu), Civic Education serves as a strategic subject in political education, particularly for first-time voters. This study employs a content analysis method with a descriptive qualitative approach, using the political education material for first-time voters as the unit of analysis. The material is sourced from the Civic Education textbook for Higher Education published by the Directorate General of Learning and Student Affairs, Ministry of Research, Technology, and Higher Education (Kemenristekdikti) in 2016. The research findings reveal that: First, the Civic Education textbook for Higher Education contains one specific chapter that discusses elections. Second, the textbook generally emphasizes the importance of national identity and democracy, aligning with the students’ profile as learners. Third, specific and crucial issues in democracy-building—such as elections, the enrichment of technical election vocabulary, and discussions on corruption and other democratic problems need stronger emphasis in the future.